Candidemia and antifungal susceptibility in Peruvian hospitals - Rios Blanco, Romina (2025)
Worldwide, Candida bloodstream infections have presented an increase in non-albicans Candida species and resistance to antifungal agents. Objective: To describe the microbiological characteristics of consecutive Candida blood culture isolates. Methods: This study analyzed 73 consecutive Candida blood isolates recovered between July 2017 and July 2019 from routine patient care at 15 Peruvian hospitals, assessing susceptibility to four antifungal agents. Results: The species most frequently detected were Candida parapsilosis 39 (53.4%), Candida albicans 23 (31.5%), and Candida tropicalis 5 (6.8%). Conclusions: All isolates were susceptible to amphotericin B, fluconazole, voriconazole, and anidulafungin. There is a predominance of non-albicans Candida cases in Peru and a high susceptibility to current antifungal drugs.